Towards retardation of slag corrosion on the lightweight alumina refractory with static magnetic field facing green metallurgy - Huang, Ao; Lian, Pengfei; Fu, Lvping; Gu, Huazhi; Zou, Yongshun (Journal of Mining and Metallurgy, Section B: Metallurgy, 2018)
Electromagnetic field is widely found and used in metallurgy and other high temperature processes, and affects the behavior of melts. The lightweight alumina based carbon free refractory is of importance for energy-saving, consumption reducing and high quality steel production, and the slag corrosion resistance is significantly concerning its service life. Does electromagnetic field control the slag corrosion behavior on the lightweight alumina refractory? In this paper, a multi-field coupled model was established to describe the slag corrosion process in an electromagnetic field. The mathematical modeling in combination of experiments was applied to clarify slag corrosion behavior of lightweight alumina refractory in static magnetic field. The simulation results agree well with that of the experiments, which mean the above model is promising for slag corrosion modeling. The results show that a static magnetic field could change properties of the molten slag and enhance the slag corrosion resistance by inhibiting slag penetration and promoting formation of a directional isolation layer, and be beneficial to clean steel production with high quality.